Analysis of Music Textbooks for Grades 5–8 in the Context of Expression of Christian Values - Kauneckas, Klaidas (Jaunųjų mokslininkų darbai, 2024)
By applying the method of content analysis, the article analyzes basic (grades 5–8) music textbooks by different authors. The article aims to find out how much and in what way Christian values are presented in the content of musical education. The results of the research revealed that the Christian faith, its meaning and values are most reflected in Balčytis’s series of textbooks “Muzika” (2007). Malikėnienė’s textbooks “Muzika” (2010) and “Muzikos labirintai” (2012) pay more attention to the development of students’ secularity and understanding of music.